Pengalaman Caregiver Pasien ODGJ Rawat Jalan Di Rumah Sakit Jiwa Prof Dr Muhammad Ildrem Medan - Irwan Silalahi (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2024)
A caregiver is someone who provides physical or emotional care for individuals who suffer from illness or disability, usually the individual is someone they love. The aim of this research is to find out how caregivers experience caring for members who experience mental disorders, with pastoral conversations with caregivers. The research method used is a qualitative method with a phenomenological approach with (in-depth interviews), early symptoms of children experiencing mental disorders, feelings that arise when hearing children experiencing mental disorders, social responses of children experiencing mental disorders (discrimination), alternatives in the treatment of children experiencing mental disorders. mental disorders, family perceptions when children experience mental disorders. The results of research conducted by the author at the Prof. Dr. Muhammad Ildrem Mental Hospital in Medan, show that there are several family members who are providing outpatient care to a family member who is ODGJ, and they are being cared for by their own family, starting from parents, older brothers, sisters, relatives, aunt, and also uncle.